Risk factors of multidrug-resistant bacterial infections among patients admitted in a tertiary care hospital of north India - Venkatesh Vaithiyam; Piyush Ranjan; Devashish Desai; Ankit Mittal; Arti Kapil; Naveet Wig; Ashutosh Biswas (Journal of Infection in Developing Countries)
Introduction: Infections with drug-resistant organisms (DRO) have been associated with poor patient outcomes. To tackle this global problem, it is necessary to understand the risk factors that predispose to infections with DRO.